A New Surgical Method for the Treatment of Acute Floating Iliofemoral Deep Vein Thrombosis in Orthopedic Patients - N. A. Trofimov; N. S. Nikolaev; A. P. Medvedev; R. N. Drandrov; Z. A. Kachaeva; А. V. Nikolskii; A. V. Edkov; S. I. Pustovalov (Креативная хирургия и онкология, 2019)
Introduction. The incidence rate of vein thrombosis stands at 180 cases per 100 thousand per year and reaches 200 cases per 100 thousand in older age population.This study aims to assess the efficacy and safety of the proposed method of retrograde vacuum aspiration performed under the conditions of increased intra-abdominal pressure in patients with iliofemoral deep vein thrombosis.Materials and methods. The analysis of surgical treatment of acute floating iliofemoral deep vein thrombosis in 52 orthopedic surgery patients following hip and knee arthroplasty. Acute floating iliofemoral deep vein thrombosis was identified in the postoperative period where the length of the floating part exceeded 4 cm. Patients received emergency treatment in the form of either the surgical prophylaxis of pulmonary embolism (study group n = 18) or a vena cava filter implantation in the infrarenal segment of the vein (control group n = 34).Results and discussion. Patency of the iliofemoral segment was completely restored after the surgery in all the 18 patients in the study group. In the control group, however,, all the 34 patients (px2 < 0.001) retained thrombotic masses in the iliofemoral segment even at the time of discharge from hospital . The length of hospital stay was also different between the comparison groups, amounting to 7 ± 0.74 days for the study group and the patients without thromboembolic complications, and to 21 ± 1.5 days (pm u — 0.0124) for the control.Conclusions 1. The new surgical method proposed for the treatment of acute floating iliofemoral deep vein thrombosis makes it possible to highly effectively restore the full patency of the vein in the shortest possible timeframe. This method is safe and more cost-effective than the classic surgical approach to the treatment of this pathology. 2. Further research into the efficacy and safety of the method proposed is needed as well as a longer term follow up on a larger number of patients.